2016
DOI: 10.1111/add.13517
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist knowledge, attitudes and confidence regarding naloxone for overdose reversal

Abstract: Community pharmacists in Australia appear to be willing to supply naloxone. Low levels of knowledge about naloxone pharmacology and administration highlight the importance of training pharmacists about overdose prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 29 publications
1
61
1
Order By: Relevance
“…13,18,25 Research has also indicated that many pharmacists are not comfortable approaching patients to discuss naloxone, are not confident in their knowledge level on overdose and naloxone, and believe that their training in the use of naloxone is insufficient. [15][16][17] In contrast, an overwhelming majority of respondents to this survey agreed that they were confident pharmacists have both sufficient knowledge and training to dispense naloxone. This result suggests a disconnection between pharmacists' confidence with naloxone and the public's confidence in pharmacists.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…13,18,25 Research has also indicated that many pharmacists are not comfortable approaching patients to discuss naloxone, are not confident in their knowledge level on overdose and naloxone, and believe that their training in the use of naloxone is insufficient. [15][16][17] In contrast, an overwhelming majority of respondents to this survey agreed that they were confident pharmacists have both sufficient knowledge and training to dispense naloxone. This result suggests a disconnection between pharmacists' confidence with naloxone and the public's confidence in pharmacists.…”
Section: Discussionmentioning
confidence: 86%
“…10 Previous research has identified numerous barriers and arguments in opposition to naloxone availability. [11][12][13][14][15][16][17][18] Some are concerned that emergency care will be neglected after naloxone administration by a layperson who is not a health care professional. This practice would be dangerous given that the half-life of naloxone is generally 1-2 hours, which is shorter than the half-life of most opioids.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…18 GPs and pharmacists are uniquely placed to engage with high-risk individuals and their friends and families. It is essential that health professionals are supported to better identify which patients need naloxone, and to train these patients appropriately.…”
mentioning
confidence: 99%